Is role stress always harmful? Differentiating role overload and role ambiguity in the challenge-hindrance stressors framework. (October 2018) - Lin, Meizhen; Ling, Qian
Abstract: This study differentiates the influences of role overload and role ambiguity on employee service quality from challenge-hindrance stressors, and explores the underlying mechanism regarding how and when such effects occur. Collecting data from 1645 employee-supervisor pairs in 49 tourism firms in China, hierarchical linear modeling results support the challenge-hindrance stressors theory by demonstrating that role overload has no effect and role ambiguity a negative effect on service quality. Analysis suggests that employee psychological empowerment fully mediates the negative effect of role ambiguity on service quality, though no similar mediating was found with role overload. Cross-level moderation analysis suggests that a supportive leadership climate triggers a positive effect of role overload on employee psychological empowerment, but does not buffer the negative effect of role ambiguity on the same. Highlights: Role overload and role ambiguity affect employee service quality differently. Role overload has no effect and role ambiguity has a negative effect on service quality. Employee psychological empowerment fully mediates the negative effect of role ambiguity on service quality. Organizational supportive leadership climate can trigger the positive role overload-psychological empowerment link. Organizational supportive leadership climate can't buffer the negative role ambiguity-psychological empowerment link.